Analisis Perbandingan Kinerja Keuangan Antar Bank Bumn Dan Industrinya Yang Terdaftar Di Bursa Efek Indonesia - Sivano, Tio Adi, Zulfa Irawati, S.E., M.Si (2015)
ABSTRACT The aim of this study was to determine the financial performance of state-owned banks, knowing the financial performance of state-owned banks Industrial and compare the financial performance of state-owned banks listed on the Indonesia Stock Exchange period in 2013, using CAMEL ratio and the ratio of Its Industry. The sampling technique in this study using purposive sampling so that the sample used in this research is PT Bank Negara Indonesia, PT Bank Rakyat Indonesia, PT Bank BTN and PT Bank Mandiri. The data analysis technique used in this research are CAMEL ratio is the aspect Capital (Capital Adequacy Ratio / CAR), assets (Assets Quality / KAP) and (Allowance for Earning Assets / PPAP), Management (Net Profit Margin / NPM), Earnings (Return On Assets / ROA) and (Operating Expenses to Operating Income / ROA), and Liquidity (Loan to Deposit Ratio / LDR) adopted from Meliangan, Steven, et al. (2014), in addition to the analysis conducted to compare the ratio of CAMEL any state-owned banks with a ratio of Its Industry. Judging from the CAMEL ratios indicate that the performance of state-owned bank listed on the Indonesia Stock Exchange has a CAR, KAP, ROA and ROA healthy, but has a provision ratio, NPM, and LDR are quite healthy. Additionally seen from the ratio of Its Industry shows that state-owned banks listed on the Indonesia Stock Exchange has a ratio of ROA and LDR are better, but has a ratio of KAP, PPAP, NPM, and ROA better than the ratio of industry, and have a CAR worse the ratio of Its Industry. The results also show that of the four state-owned banks are the most excellent performance of Bank BRI and the worst performance of Bank BTN is well seen by the ratio and the ratio CAMEL Industry-although in general the performance of state-owned banks showed healthy performance. Keywords: Financial Performance, State-owned banks, Industrial Bank SOE